Multiple Activities of LigB Potentiate Virulence of Leptospira interrogans: Inhibition of Alternative and Classical Pathways of Complement - Choy, Henry A. (Public Library of Science, 2012)
Microbial pathogens acquire the immediate imperative to avoid or counteract the formidable defense of innate immunity as soon as they overcome the initial physical barriers of the host. Many have adopted the strategy of directly disrupting the complement system through the capture of its components, using proteins on the pathogen's surface. In leptospirosis, pathogenic Leptospira spp. are resistant to complement-mediated killing, in contrast to the highly vulnerable non-pathogenic strains. Pathogenic L. interrogans uses LenA/LfhA and LcpA to respectively sequester and commandeer the function of two regulators, factor H and C4BP, which in turn bind C3b or C4b to interrupt the alternative or classical pathways of complement activation. LigB, another surface-proximal protein originally characterized as an adhesin binding multiple host proteins, has other activities suggesting its importance early in infection, including binding extracellular matrix, plasma, and cutaneous repair proteins and inhibiting hemostasis. In this study, we used a recent model of ectopic expression of LigB in the saprophyte, L. biflexa, to test the hypothesis that LigB also interacts with complement proteins C3b and C4b to promote the virulence of L. interrogans. The surface expression of LigB partially rescued the non-pathogen from killing by 5% normal human serum, showing 1.3- to 48-fold greater survival 4 to 6 d following exposure to complement than cultures of the non-expressing parental strain. Recombinant LigB7′-12 comprising the LigB-specific immunoglobulin repeats binds directly to human complement proteins, C3b and C4b, with respective K(d)s of 43±26 nM and 69±18 nM. Repeats 9 to 11, previously shown to contain the binding domain for fibronectin and fibrinogen, are also important in LigB-complement interactions, which interfere with the alternative and classical pathways measured by complement-mediated hemolysis of erythrocytes. Thus, LigB is an adaptable interface for L. interrogans to efficiently counteract the multiple homeostatic processes of the host.